2014
DOI: 10.1007/s11033-014-3560-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of calpain inhibitor N-acetyl-l-leucyl-l-leucyl-l-norleucinal on acute alcohol consumption related cardiomyopathy

Abstract: Excessive alcohol consumption and alcoholism cause medical problems with high mortality and morbidity rates. In this study we aimed to decrease the alcohol related tissue damage by inhibiting calpain activation which plays an important role in apoptosis and necrosis, in rats with cardiomyopathy induced by acute alcohol consumption. Male Sprague-Dawley rats were separated into four groups (control, vehicle, alcohol and alcohol + inhibitor) with 10 rats in each. Control group received isocaloric maltose while ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The use of Annexin V staining with fluorescence-activated cell sorting has confirmed an alcohol-mediated increase in apoptosis in cardiomyocytes (94, 95). Similarly, the number of apoptotic nuclei detected via TUNEL was increased after acute alcohol in male mice (3 day, 3 g/kg alcohol/day) (20) and male rats (8 g/kg alcohol) (96), as well as in H9c2 cardiomyocytes (100–400 mg/dL, 24 hr), neonatal rat cardiac myocytes (200 mM, 4 hr) and primary cardiomyocytes from adult rats (0.3–0.5% alcohol in media, 4 days). This effect appears specific to cardiomyocytes as there was no detectable increase in apoptosis in alcohol-treated cardiac fibroblasts (97).…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Annexin V staining with fluorescence-activated cell sorting has confirmed an alcohol-mediated increase in apoptosis in cardiomyocytes (94, 95). Similarly, the number of apoptotic nuclei detected via TUNEL was increased after acute alcohol in male mice (3 day, 3 g/kg alcohol/day) (20) and male rats (8 g/kg alcohol) (96), as well as in H9c2 cardiomyocytes (100–400 mg/dL, 24 hr), neonatal rat cardiac myocytes (200 mM, 4 hr) and primary cardiomyocytes from adult rats (0.3–0.5% alcohol in media, 4 days). This effect appears specific to cardiomyocytes as there was no detectable increase in apoptosis in alcohol-treated cardiac fibroblasts (97).…”
Section: Apoptosismentioning
confidence: 99%
“…Under in vitro conditions, pro-caspase 3/active caspase 3 protein expression was increased in endothelial progenitor cells (25 mM, 48 hr) (100), while cleaved caspase 3 was increased in H9c2 cells (100–400 mM, 24 hr) and neonatal rat cardiac myocytes (200 mM, 4 hr) (89, 95). In contrast, caspase 3 activity was unchanged in rat hearts in response to acute alcohol intoxication, despite increased caspase 3 staining in isolated cardiomyocytes (96). Therefore, the majority of recent data indicate that caspase 3 is increased in response to acute and chronic alcohol indicating apoptotic pathway activation.…”
Section: Apoptosismentioning
confidence: 99%
“…Calpain-1 belongs to the family of cysteine proteases. Calpain-1 activation has been demonstrated to induce IκBα degradation and NF-κB activation [7]. In a previous study, we found that calpain-1 plays an critical role in atherogenesis through endothelial disorder and inflammation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it inhibits the cytochrome c oxidase (or complex IV) of the mitochondrial respiratory chain, resulting in a blockage of adenosine-triphosphate synthesis. The suggested mechanism of the cardiac toxicity is an increase in intracellular calcium, due to an increased influx, which activates calpain, a protease responsible for intracellular damages causing cell apoptosis through the caspase pathway 4,5,6 . Despite interesting results of calcium antagonists in vitro no human case of NaN3 poisoning treated with calcium antagonist has been reported yet.…”
mentioning
confidence: 99%